ICT interventions impacting big societal challenges: an electronic healthcare approach to homelessness. (2015) - Ahluwalia, Punit; Gimpel, Gregory; Varshney, Upkar
This paper investigates how electronic healthcare technology can address a pervasive societal problem: homelessness. Mental illness, a leading cause of homelessness, can be treated successfully with proper medication. Few psychiatric patients, however, adhere to the medication regimen prescribed by their doctors. We employ a systems thinking approach to model the multi-dimensional decision system by which patients choose whether or not to take medication. We identify that interventions raising patients' self-efficacy will significantly improve medication adherence among mentally ill patients and that it can translate into a reduction of homelessness. This paper makes two key research contributions: it calls attention to the study of medication adherence within electronic healthcare research and it proposes a systems dynamics model that highlights how, when addressing complex societal challenges, affordances during one time period can become constraints in another.